Separation and Crystal Structure of Two Isomeric of 1,3,3-Trimethyl-5-nitro-3-(4-nitrophenyl)-2,3-dihydro-1H-indene and 1,3,3-Trimethyl-5-nitro-1-(4-nitrophenyl)-2,3-dihydro-1H-indene - Wang, Y.; Wu, D.F.; Shao, T.; Men, J.; Gao*, G.W. (Asian Journal of Chemistry, 2014)
The isomers, 1,3,3-trimethyl-5-nitro-3-(4-nitrophenyl)-2,3-dihydro-1H-indene (1) and 1,3,3-trimethyl-5-nitro-1-(4-nitrophenyl)-2,3-dihydro-1H-indene (2), have been prepared and separated effectively. Their crystal structures can not be confirmed by the results of IR, 1H NMR, 13C NMR and MS studies, but determined by X-ray diffraction. The structure identity has explained the precise configurations of title compounds. DSC/TG analysis illustrate that the isomers 1 and 2 possess excellent thermal stability.